Analisis Komposisi Giro, Tabungan dan Deposito Terhadap Profitabilitas Perusahaan - Oktawidya Tirta , Catur; Zanaria, Yulita; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the composition of current accounts, savings and deposits on profitability at PT. Bank Cipta Dana Mulia. Data analysis is done by Miles and Huberman Model Analysis. The results of the study indicate that the relatively low interest rate of current accounts and the contribution to the composition of third party funds as a whole so far, provide confidence that current accounts have an influence on achieving net interest income and the greater the current accounts that are successfully collected, the greater the contribution to achieving net interest income. Savings funds have an influence, although not too large, on achieving profit. However, the risk of liquidity needs from these savings funds is also relatively large because the fluctuation of funds from these savings funds is relatively very high in line with the ease and facilities of withdrawal and for that it is necessary to maintain its liquidity needs. The relatively high interest rate of deposit funds and the contribution to the composition of third party funds as a whole so far, it can be concluded that deposit funds have a fairly large influence on achieving net interest income